The effect of nitrogen fertilizers on productivity of spring triticale in the dry steppe zone of Kazakhstan - R. Kh. Ramazanova; A. E. Tursinbaeva; G. R. Kekilbaeva; A. E. Matina; A. .. Kasipkhan (Аграрная наука Евро-Северо-Востока, 2018)
Provision of stable grain production ensures food security for any state. Wheat is the main grain crop in Kazakhstan. But harsh climate does not allow to get high yields on the regular. Therefore, it is necessary to find grain reserves by introducing other grain crops. Triticale has been focused on here recently though it is not widely spread, and its cultivation technology, including the use of fertilizers, almost has not been studied yet. The aim of the research is to study the effect of nitrogen fertilizers on the yield and grain quality of spring triticale on dark chestnut soils of the Akmola region of Kazakhstan. The object of the research is spring triticale of Amigo variety. In 2015-2017 the rates and time of nitrogen application were studied. The climatic conditions during the years of research differed both by temperature range and the amount of rainfall during the vegetation period. On average for three years the highest yield (1.98 t/ha) was obtained on P60 background in variants: N60 before sowing; N30 before sowing in complex with N30 during the tillering phase. With nitrogen application on P60 background the yield increase was 0.55-0.7 t/ha, the protein content in triticale grain raised from 7.6 to 9.9-10.7%. Increase in fertilizer rates led to rise in grain yields, but payback of 1 kg of acting matter of fertilizer in grain has reduced. The greatest return of 1 kg of the acting matter was obtained by applying N30 during the tillering phase on phosphorus-free background -10.2-10.4 kg of grain. To increase the yield and quality of spring triticale the variant with nitrogen application at rate N60 both by single and dosing application on P60 background is recommended.